PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KAHOOT TERHADAP MINAT BELAJAR SISWA KELAS X SMA NEGERI 7 PEKANBARU PADA MA-TA PELAJARAN PENDIDIKAN PANCASILA - Mayang Agustina; Jumili Arianto; Supentri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of Kahoot learning media on the learning interest of tenth-grade students at SMA Negeri 7 Pekanbaru in Pancasila Education. The study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of 336 students, while the sample included 70 students divided into an experimental class and a control class. Data were collected through a learning-interest questionnaire covering enjoyment, student involvement, attention and concentration, and learning attraction. Data were analyzed using descriptive statistics, normality tests, homogeneity tests, Independent Sample t-Test, and Cohen’s d effect size analysis. The results showed that Kahoot had a positive and significant effect on students’ learning interest, with a significance value of 0.000 < 0.05. The experimental class mean score increased from 57.83 to 68.29, while the control class reached 57.91. Cohen’s d value of 1.47 indicated a large effect. Therefore, Kahoot is effective in improving students’ learning interest in Pancasila Education.